Narrative Interaction in Family Dinnertime Conversations - Bohanek, Jennifer G.; Fivush, Robyn; Zaman, Widaad; Lepore, Caitlin E.; Merchant, Shela; Duke, Marshall P. (Merrill-Palmer Quarterly, 2009)
Reminiscing has been shown to be a critical conversational context for the development of autobiographical memory, self-concept, and emotional regulation (for a review, see Fivush, Haden, & Reese, 2006). Although much past research has examined reminiscing between mothers and their preschool children, very little attention has been given to family narrative interaction with older children. In the present study, we examined family reminiscing in spontaneous narratives that emerged during family dinnertime conversations. The results revealed that mothers contributed more to the narratives than did fathers in that they provided, confirmed, and negated more information, although fathers requested more information than mothers. In exploratory analyses, mothers' contributions to shared family narratives were found to be related to fewer internalizing and externalizing behaviors in their children, while fathers' contributions to individual narratives of day-to-day experiences were related to fewer internalizing and externalizing behaviors in their children. These results indicate that mothers and fathers may play different roles in narrative construction with their children, and there is some suggestion that these differences may also be related to children's behavioral adjustment.